Ciri Khas dan Perkembangan Pendidikan Anak-Anak di Kuttâb pada Zaman Nabi Muhammad SAW - Zainal Mutaqin (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2023)
This research is the result of library research. This research is to answer three problems, namely when was early childhood education at the time of the Prophet SAW born, what was the form of the institution, and how was it developed. The research data was collected through reading texts from educational books, history, and other classic books. then analyzed by qualitative descriptive method. The results of the study concluded that the existence of Kuttâb as an educational institution for its children grew at the time of the Prophet s.a.w, especially after the migration event, the need for the ability to write and read for children was seen in the events of redemption of prisoners of war by teaching reading and writing to Muslim children in Medina. Along with the increasing number of friends who studied the Qur'an and wrote Dar Al Qurra' was born in Medina which is considered as the forerunner to the birth of Kuttâb or mahdzarah. In its development educational institutions for these children. Portrait of Kuttâb's education during the lifetime of Rasulullah s.a.w. at first it only taught writing and reading, but over time the subject matter was added which is the specialty of Kuttab, namely the Qur'an. The addition of Al-Qur'ân subject matter in Kuttâb is a characteristic of Kuttâb education in the Islamic world and at the same time is a reason for some historians who argue that Kuttâb in the Islamic world only emerged during the caliphate of Abu Bakr RA.